Behavior of morpholine and its trimethylsilyl derivative in reactions with trimethylsilyl isocyanate - L. O. Belova; N. A. Golub; M. V. Pletneva; N. I. Kirilina; A. D. Kirilin (Тонкие химические технологии, 2022)
Objectives. To study the patterns of behavior of morpholine and its trimethylsilyl derivative in reactions with trimethylsilyl isocyanate.Methods. The study employed infrared and nuclear magnetic resonance spectroscopy, as well as elemental analysis.Results. The formation of mixtures of tautomeric forms of silicon-containing urea—N-(trimethylsilyl) morpholine-4-carboxamide and trimethylsilylmorpholine-4-carboximidoate—was established.Conclusions. It is shown that the composition and structure of the resulting products are determined both by the presence of a morpholine substituent at the nitrogen atom and by the type of isocyanate used. Unlike the trimethylsilyl derivative of morpholine, morpholine itself reacts with trimethylsilyl isocyanate to form a mixture of tautomeric forms.